Effects of ionic liquid and nanofiller to the physicochemical properties of poly (Ethyl Methacrylate) based polymer electrolytes / Nur Fatinah Muhamad Zain - Nur Fatinah, Muhamad Zain (2016)
Three different series of polymer electrolytes based on poly (ethyl methacrylate) (PEMA) were successfully developed by solution casting technique. Pure PEMA are highly crystalline in nature; exhibiting glass transition temperature (Tg) of ~ 70 ºC with low room temperature ionic conductivity of 10-11 S cm-1. In order to suppress this crystalline behaviour, the polymers were incorporated with various amounts of room temperature ionic liquid (RTIL), namely 1-ethyl-3-methylimidazolium bis(trifluorosulfonyl) imide (EMITFSI) as a plasticizer. This first series of polymer electrolytes was labeled as System I. The sample containing 40 wt.% EMITFSI showed a maximum room temperature ionic conductivity of 5.41 × 10-7 S cm-1 and thermal stability up to 300 ºC. System II was prepared by adding both EMITFSI and magnesium triflate (MgTf2) in the polymer matrix in order to study the effects of addition of both ionic liquid and salt to the properties of PEMA. The interaction between PEMA, EMITFSI and MgTf2 was confirmed using FTIR by the shifts of significant bands of C=O and C-O-C2H5 groups in PEMA that are capable to coordinate with the cation of a salt and ionic liquid. The presence of amorphous phase was observed from SEM analysis for the highest conducting samples for System I and System II. The ionic conductivity obtained was 1.72 × 10-6 S cm-1 at room temperature for PEMA-20 wt.% MgTf2-30 wt.% EMITFSI electrolyte. However, the composition of PEMA-20 wt.% MgTf2-40 wt.% EMITFSI could not produce free-standing film. Nanocomposite polymer electrolytes (NCPEs) (System III) were prepared in order to study the effects of magnesium oxide (MgO) nanofiller to ionic liquid retention properties of polymer-salt-ionic liquid electrolytes. NCPEs were prepared by adding different compositions of nanosized MgO as ceramic nanofiller in PEMA-20 wt.% MgTf2-40 wt.% EMITFSI electrolytes. The addition of MgO nanofiller has improved the film stability and ionic liquid retention property of the sample containing 20 wt.% MgTf2 and 40 wt.% iii EMITFSI. The room temperature ionic conductivity was improved up to 10-5 S cm-1 by the incorporation of 1 wt.% of MgO nanofiller in the polymer electrolytes film. Temperature-dependence ionic conductivity for all systems showed Arrhenius-like behavior. The highest ionic conductivity was observed for NCPE film with the value of 3.78 × 10-4 S cm-1 at 100 ºC. Enhancement of electrochemical potential stability window determined by LSV was observed for System II and System III, due to the impregnation of ionic liquid and ceramic nanofiller. This indicated that NCPE system has the potential for use as an electrolyte in magnesium ion batteries.